NEAR SURFACE GEO-ELECTRIC STUDY OF OSHOSUN VILLAGE AND ITS ENVIRONS FOR ENGINEERING PURPOSES (FULafia Journal of Science and Technology, 2021)
The near surface investigation of Oshosun community and its environ was carried out in order to delineate the geotechnical properties of the subsurface layers in anticipation of engineering construction purposes. Integrated methods of geophysical and geotechnical techniques were deployed to characterize the nature and competence of the subsurface strata prior to construction of foundation for engineering structures. The geophysical technique employed involved 2-D Electrical Resistivity Imaging (ERI) while Standard Penetration Tests (SPT) were used as geotechnical methods. The 2-D ERI were acquired in outlined three different sites within the study area. Five traverses of 2-D ERI were established and an SPT borehole data was obtained from each site. The 2-D ERI data were processed with DiprofWin software to obtain the 2-D resistivity structure.
Keywords: Near Surface; Geophysical; Restivity; Oshosun; 2-D ERI